2022
DOI: 10.1590/1980-5373-mr-2022-0179
|View full text |Cite
|
Sign up to set email alerts
|

Pitting and Crevice Corrosion Behavior of the Duplex Stainless Steel UNS S32205 Welded by Using the GTAW Process

Abstract: This study investigated the pitting and crevice corrosion behavior of the gas tungsten arc welding (GTAW) process in the UNS S32205 according to industrial parameters. Results revealed that the welding process presented a weld metal chemical composition similar to the base metal and an adequate balance of the austenite and ferrite phases. No relevant variation in the hardness was observed and XRD spectra did not identify the presence of deleterious phases in the weld bead. Cyclic polarization tests revealed si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…This scale was formed by microbiologically induced calcium carbonate precipitation (MICP) [31,33]. The microstructural examination revealed that corrosion attack occurred preferentially along the austenite grains; this phenomenon is common in duplex stainless steel, which typically fails due to crevice corrosion [39,40]. The use of materials that are inappropriate for the heat exchangers' seawater cooling medium conditions is the leading/root cause of this issue.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This scale was formed by microbiologically induced calcium carbonate precipitation (MICP) [31,33]. The microstructural examination revealed that corrosion attack occurred preferentially along the austenite grains; this phenomenon is common in duplex stainless steel, which typically fails due to crevice corrosion [39,40]. The use of materials that are inappropriate for the heat exchangers' seawater cooling medium conditions is the leading/root cause of this issue.…”
Section: Discussionmentioning
confidence: 99%
“…A preferential attack on the austenite grain of the weld metal phenomenon was observed during the crevice corrosion test. According to prior studies, preferential dissolution occurs at all morphologies of austenitic phases: grain boundary (GBA), Widmanstätten (WA), and intragranular (IGA) [38][39][40]. The corrosion attack on the tube sheet was caused by crevice corrosion between the surface deposit (bacteria product) on the tube sheet surface and the substrate.…”
Section: Microstructural Examinationmentioning
confidence: 99%
See 3 more Smart Citations